The Impact Celebrity Endorsement, Information Quality, And Perceived Risk On Purchase Decision: a Case of Online Shopping Batik Jogja - Febrianti, R Adjeng Mariana; Chotim, Endah Ratnawaty; Hafidh, Abdul Ahmad; Octavian, Rizky Ferari (CENTRAL ASIA AND THE CAUCASUS, 2022)
In the current era of globalization, the impact of technology has affected all aspects of life, especially in business practices. Celebrity support for promotion has become a phenomenon that many business people do to increase their sales. Social media has now become a tool for consumers to get information about what they need. However, information that is often circulated on business platforms is currently one of the obstacles for consumers when they want to make a purchase. This study was proposed to determine whether celebrity endorsement, information quality, and perceived value have an influence on online purchasing decisions? If it is influential, what is the percentage of the influence. This study uses an explanatory method approach, where the position of each variable explains the causal relationship. The sample in this study was selected as many as 125 consumers who were in the city of Jogja. The results of the descriptive analysis show that the responses to each variable and question are in the good category. Based on the results of the coefficient of determination adjusted R square test results obtained a value of 67.5%. This shows that the three variables have a strong influence in influencing online purchasing decisions on batik jogja. Therefore, this study has proven that these three variables can be used as one of the strategies used in entering the global market so that a competitive advantage is obtained. The limitation of this research is that the respondents are only limited to certain industries, namely the batik industry. It is hoped that further research can be carried out with a different scope and with a larger sample and also use other variables that may influence online purchasing decisions.